Divisive Normalization and Neuronal Oscillations in a Single Hierarchical Framework of Selective Visual Attention - Montijn, Jorrit S.; Klink, P. C.; Van Wezel, Richard J. (Frontiers in Neural Circuits, 2012)
In divisive normalization models of covert attention, spike rate modulations are commonly used as indicators of the effect of top-down attention. In addition, an increasing number of studies have shown that top-down attention increases the synchronization of neuronal oscillations as well, particularly those in gamma-band frequencies (25 to 100 Hz). Although modulations of spike rate and synchronous oscillations are not mutually exclusive as mechanisms of attention, there has thus far been little effort to integrate these concepts into a single framework of attention. Here, we aim to provide such a unified framework by expanding the normalization model of attention with a time dimension; allowing the simulation of a recently reported backward progression of attentional effects along the visual cortical hierarchy. A simple hierarchical cascade of normalization models simulating different cortical areas however leads to signal degradation and a loss of discriminability over time. To negate this degradation and ensure stable neuronal stimulus representations, we incorporate oscillatory phase entrainment into our model, a mechanism previously proposed as the communication-through-coherence (CTC) hypothesis. Our analysis shows that divisive normalization and oscillation models can complement each other in a unified account of the neural mechanisms of selective visual attention. The resulting hierarchical normalization and oscillation (HNO) model reproduces several additional spatial and temporal aspects of attentional modulation.